PENGARUH KOMPETENSI GURU DAN SELF DIRECTED LEARNING TERHADAP HASIL BELAJAR MATA PELAJARAN FIKIH PADA SISWA KELAS VIII MTsN 17 JAKARTA TAHUN PELAJARAN 2018/2019 - Abdul Rasyid (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2019)
The purposes of this research are: (1) To know the influence of teacher competence on learning achievement of FIQH subject at the eight grade student of MTsN 17 Jakarta, (2) To know the influence of self directed learning on learning achievement of FIQH subject at the eight grade student of MTsN 17 Jakarta, (3) To know the influence of teacher competence and self directed learning simultanously on learning achievement of FIQH subject at the eight grade student of MTsN 17 Jakarta The writer took sample of 127 the eight grade students of MTsN 17 Jakarta. The kinds of data were questionnaire and documentation. To analize data the writer used product moment correlation analysis. The conclusions of this research are as follows: teacher competence influences on learning achievement of FIQH subject 17,4%, self directed learning influences on learning achievement of FIQH subject 15,5% , teacher competence and self directed learning simultanously on learning achievement of FIQH subject 36,4%.